Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/en14206847
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thermochemical Heat Storage Based on CaO/CaCO3 Cycles: A Review

Abstract: Due to the inconsistency and intermittence of solar energy, concentrated solar power (CSP) cannot stably transmit energy to the grid. Heat storage can maximize the availability of CSP plants. Especially, thermochemical heat storage (TCHS) based on CaO/CaCO3 cycles has broad application prospects due to many advantages, such as high heat storage density, high exothermic temperature, low energy loss, low material price, and good coupling with CSP plants. This paper provided a comprehensive outlook on the integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 141 publications
0
10
0
Order By: Relevance
“…As a matter of fact, materials with a weak ability to collect solar energy either directly, via absorption of the solar radiation, or indirectly, via conduction, make it difficult to reach the high temperature needed to drive the endothermic calcination reaction . Therefore, the improvement of the sorbent optical and thermal conduction properties represents one of the most crucial challenges in the framework of CaL-TCS for CSP applications …”
Section: Thermochemical Energy Storage (Tcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, materials with a weak ability to collect solar energy either directly, via absorption of the solar radiation, or indirectly, via conduction, make it difficult to reach the high temperature needed to drive the endothermic calcination reaction . Therefore, the improvement of the sorbent optical and thermal conduction properties represents one of the most crucial challenges in the framework of CaL-TCS for CSP applications …”
Section: Thermochemical Energy Storage (Tcs)mentioning
confidence: 99%
“…More specifically, two reviews are focused on a very specific aspect of the process: Fedunik-Hofman et al reviewed the kinetics of solid–gas reactions and their application to carbonate looping systems for both CCS and TCS applications; likewise, Ortiz et al critically assessed the technology needed to scale up the Ca-Looping process for both CCS and TCS applications. Yang et al, Khosa et al, and Ortiz et al, on the contrary, addressed the process in a more systematic and extensive way, namely, not focusing on only one aspect of the process; however, these three reviews are specific on the CaCO 3 /CaCO couple, i.e., not considering other alternative carbonate systems.…”
Section: Thermochemical Energy Storage (Tcs)mentioning
confidence: 99%
“…According to the carbonation kinetics of limestone, 49 the reaction heat release of individual particles, Q r , can be expressed by eqn (11):…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…6 An inert gas such as He or N 2 is generally used in the calcination stage so that CaCO 3 can be fully calcined. 11 Due to the high thermal conductivity of He and the fast diffusion of CO 2 in He, the decomposition rate of CaCO 3 in He is faster than that in N 2 . 12 Another advantage of calcination in a He atmosphere is that the calcination temperature can be reduced to 725 °C, 13 which reduces the construction cost of the heliostat field 14 and the radiation heat loss.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [21] evaluated the thermal insulation and heat storage performance of the brick-polystyrene board composite wall according to a 10 d determination, and stated that the wall with external polystyrene board exhibited better thermal insulation performance than the wall with inbuilt polystyrene board. Agrafiotis et al [22][23][24] reported a new type of porous ceramic-foam heat storage material, and a type of solar redox powder was added to this material to improve its heat storage performance. However, although the application of the abovementioned new materials or structures significantly improves the heat preservation performance of the greenhouse, the construction costs of these walls are relatively high, which is adverse to the extensive promotion.…”
Section: Introductionmentioning
confidence: 99%